ANALISIS NILAI-NILAI KARAKTER DAN NILAI NILAI MATEMATIKA MELALUI PERMAIANAN TRADISIONAL MADURA PADA SISWA SEKOLAH DASAR - Agusriyanti Puspitorini (Institut Dirosat Islamiyah Al-Amien Prenduan, 2019)
The purpose of this study is to describe the mathematical concepts and character values found in traditional Madurese games at SDN Aeng Baja Raja Bluto. The samples in this study were fourth grade students at SDN Aengbaja Raja, Bluto District. The instruments used in this study were observation sheets and interviews as well as documentation. From the results of the study it can be described that the mathematical values contained in traditional Madurese games include the concept of distance, addition operations, multiplication, and recognizing multiple numbers and affective elements that can be created from traditional Madurese games, while character values that can be built through games Traditional values are togetherness, mutual cooperation, fairness, integrity, honesty.